Foreign Exchange Risk Regulation : Issues for Industrial and Developing Countries - Hartmann, Philipp (IMF Working Papers; Working Paper ;, 1994)
Capital adequacy regulations or quantity restrictions on bank portfolios put forward by the Basle Committee on Banking Supervision have virtually become an international standard of prudential regulation. Recent proposals aim at extending this approach to market risks, in particular to foreign exchange risk. The present paper provides a critical analysis of proposals to introduce foreign exchange position limits on a uniform cross-country basis, focusing on their effectiveness and their possible impact on the functioning of both mature and developing foreign exchange markets. Theoretical considerations are underpinned in the paper with descriptions of existing or proposed regulations, in a broad range of both industrial and developing countries. Experiences with the use of foreign exchange position limits in developing countries provide insight into their widespread use for other than prudential purposes, in particular to support exchange rate and exchange control policies.